2011
DOI: 10.1016/j.solmat.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Extended description of tunnel junctions for distributed modeling of concentrator multi-junction solar cells

Abstract: One of the key components of highly efficient multi-junction concentrator solar cells is the tunnel junction interconnection. In this paper, an improved 3D distributed model is presented that considers real operation regimes in a tunnel junction. This advanced model is able to accurately simulate the operation of the solar cell at high concentrations at which the photogenerated current surpasses the peak current of the tunnel junction. Simulations of dual-junction solar cells were carried out with the improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The equivalent resistance should be as low as possible to avoid being the limiting vertical component in the series resistance of the device . Besides, a high peak tunneling current is desirable to be well above the photocurrent generated by the solar cell under concentration; withstand peak irradiances on the cell arising from non‐uniform illumination profiles created by the optics of CPV modules ; and increase the margin for the eventual degradation of their performance after the thermal load originated during the growth of subsequent subcells in a MJSC stack .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent resistance should be as low as possible to avoid being the limiting vertical component in the series resistance of the device . Besides, a high peak tunneling current is desirable to be well above the photocurrent generated by the solar cell under concentration; withstand peak irradiances on the cell arising from non‐uniform illumination profiles created by the optics of CPV modules ; and increase the margin for the eventual degradation of their performance after the thermal load originated during the growth of subsequent subcells in a MJSC stack .…”
Section: Introductionmentioning
confidence: 99%
“…withstand peak irradiances on the cell arising from non‐uniform illumination profiles created by the optics of CPV modules ; and…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been carried out for making the light impinging the solar cell more uniform . However, in regard to the TJ's limitation, it has been observed that under certain circumstances, the solar cell's short circuit current may be higher than the peak current of the TJ without causing an efficiency loss . Accordingly, this paper seeks to first illustrate the behavior of multijunction solar cells under spatial and spectral non‐uniform light profiles to finally clarify the real limitations imposed by TJs in typical optical designs.…”
Section: Introductionmentioning
confidence: 99%
“…Current which has to be injected in darkness to emulate working conditions. For that simulations with our 3D distributed model for triple-junction solar cells have been carried out [5], [6]. The criterion followed has been that the absolute value of current density through the junctions in darkness does not surpass at any point of the solar cell the current density photo-generated in the active area at 820 X [4].…”
Section: Design Of the Testmentioning
confidence: 99%